Stochastic quantum inflation for a canonical scalar field with linear self-interaction potential - Grigoris Panotopoulos (European Physical Journal C: Particles and Fields, 2017)
Abstract We apply Starobinsky’s formalism of stochastic inflation to the case of a massless minimally coupled scalar field with linear self-interaction potential. We solve the corresponding Fokker–Planck equation exactly, and we obtain analytical expressions for the stochastic expectation values.